2017
DOI: 10.2131/jts.42.789
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to tetrabromobisphenol A (TBBPA), a brominated flame retardant, exacerbated the pneumonia in respiratory syncytial virus (RSV)-infected offspring mice

Abstract: -To investigate the effects of perinatal exposure to tetrabromobisphenol A (TBBPA), a brominated flame retardant, on the immune system, a respiratory syncytial virus (RSV) infection mouse model was utilized. Female mice were exposed to TBBPA mixed with the diet from 10 days after conception to weaning on postnatal day 21. Offspring mice were infected intranasally with A2 strain of RSV. Although no general toxicological sign was observed, the pulmonary viral titers of offspring mice exposed to 0.1% TBBPA were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The main marker used to monitor TBBPA effects on immune system is the production of cytokines. For example, this is the case of tumor necrosis factor alpha ( Tnf-α ), interferon γ ( Ifnγ ) or Il-4/6/8/24 ( Watanabe et al, 2010 , 2017 ; Koike et al, 2013 ; Park et al, 2014 ; Almughamsi and Whalen, 2016 ). In another study Wang et al ( Wang et al, 2019 ) found that macrophages exposed to TBBPA over-express pro-inflammatory cytokines ( Il-1β , Il-6 , and Tnf-α ), together with a reduced expression of antigen-presenting-related genes (including Cd86 , DE in our datasets).…”
Section: Discussionmentioning
confidence: 99%
“…The main marker used to monitor TBBPA effects on immune system is the production of cytokines. For example, this is the case of tumor necrosis factor alpha ( Tnf-α ), interferon γ ( Ifnγ ) or Il-4/6/8/24 ( Watanabe et al, 2010 , 2017 ; Koike et al, 2013 ; Park et al, 2014 ; Almughamsi and Whalen, 2016 ). In another study Wang et al ( Wang et al, 2019 ) found that macrophages exposed to TBBPA over-express pro-inflammatory cytokines ( Il-1β , Il-6 , and Tnf-α ), together with a reduced expression of antigen-presenting-related genes (including Cd86 , DE in our datasets).…”
Section: Discussionmentioning
confidence: 99%
“…DNA microarray analysis was performed as previously reported (Furuichi et al, 2011;Watanabe et al, 2017). Intensity values of each scanned feature were quantified using Agilent Feature Extraction software version 11.5.1.1, which performs background subtractions.…”
Section: Microarray Analysismentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) causes pneumonia and bronchitis, mainly in infants, children, and elderly people with underlying diseases (Griffiths et al, 2017). In our previous research, we evaluated the effects of various nanomaterials and bacterial particles on the pathology of RSV pneumonia in mice, and investigated the toxicity and effects of these particles on the immune system (Watanabe et al, 2017;Miyauchi et al, 2019). In addition, we confirmed that intranasal administration of MWCNT to RSV-infected mice caused immune system cells in the bronchioles and alveoli to react to the carbon fibers and exacerbated RSV pneumonia (Hashiguchi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%